Gestión de talento humano y su relación en el desempeño laboral en la unidad distrital de educación Quevedo - Mocache 12d03, cantón Quevedo, año 2014. Quevedo - Moreira Segovia, Rosa Vanessa (2015)
The Human Talent is one of the most important resources in all types of institutions, as should assess this area permanently, applying techniques and management audits, it must determine the level of compliance of the established functions in the structural member. This present research is based on a study of the management of Human Talent that contributes to the District Education Unit Quevedo – Mocache 12D03 to get a clearer vision of the basic processes and develop new skills to help motivate and get a good work performance. The management og Human Talent of the District Unit 12D03 Quevedo – Mocache Education repose in a complex structure of formal relations linking the dependencies between them, also has the own risk of managing the Human resources appropriately, according to the professional profile and according to the law too, with the purpose to get objectives and planned goals….